2016
DOI: 10.1007/s10545-016-9978-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy as presenting sign of glycogenin‐1 deficiency—report of three cases and review of the literature

Abstract: We describe a new type of cardiomyopathy caused by a mutation in the glycogenin-1 gene (GYG1). Three unrelated male patients aged 34 to 52 years with cardiomyopathy and abnormal glycogen storage on endomyocardial biopsy were homozygous for the missense mutation p.Asp102His in GYG1. The mutated glycogenin-1 protein was expressed in cardiac tissue but had lost its ability to autoglucosylate as demonstrated by an in vitro assay and western blot analysis. It was therefore unable to form the primer for normal glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“… 6 8 , 12 , 13 In reported cases of glycogenin deficiency, skeletal muscle involvement was always that of a limb-girdle myopathy, accompanied in some instances by an additional distal involvement. 6 13 Cardiomyopathy in patients with GSDXV is rare, 6 , 14 but mutations in the GYG1 gene can be observed with no skeletal muscle signs. 14 …”
mentioning
confidence: 99%
“… 6 8 , 12 , 13 In reported cases of glycogenin deficiency, skeletal muscle involvement was always that of a limb-girdle myopathy, accompanied in some instances by an additional distal involvement. 6 13 Cardiomyopathy in patients with GSDXV is rare, 6 , 14 but mutations in the GYG1 gene can be observed with no skeletal muscle signs. 14 …”
mentioning
confidence: 99%
“…6a). Furthermore, through literature research, we found that 9 MYC target genes were previously reported involving the development of heart failure, including STAT3 [48], PRMT1 [49], PRKCH [50], HSPA4 [51], DDX3X [52], GYG1 [53], GADD45B [54] and PKN1 [55] (Fig. 6a, the red ones).…”
Section: The Myc and C/ebpβ Mediated Transcriptional Networkmentioning
confidence: 74%
“…Muscle biopsies show the accumulation of polyglucosan bodies, consisting of hyper‐intense periodic acid‐Schiff (PAS)‐positive material with a variable resistance to alpha‐amylase treatment. Although cardiac involvement has been reported in 4 patients with glycogenin‐1 gene ( GYG1 ) mutations, these patients did not show any clear evidence of skeletal muscle disease …”
mentioning
confidence: 76%
“…Although cardiac involvement has been reported in 4 patients with glycogenin-1 gene (GYG1) mutations, these patients did not show any clear evidence of skeletal muscle disease. 8,9 Here, we describe a 63-year-old woman born to consanguineous French parents, who developed right shoulder pain, difficulty climbing stairs and left foot weakness causing stumbling episodes at 46 years of age. Over time, the patient reported increasing difficulty elevating the right arm.…”
mentioning
confidence: 99%
See 1 more Smart Citation